Multidimensional analogs of A. Bicardze system - Paliokas, Eugenijus (Lietuvos matematikos rinkinys, 2001)
The problem of classification of elliptic partial differential systems is studied. Two classes of multidimensional elliptic systems are defined, that are to be considered multidimensional analogs of strongly connected and weekly connected elliptic systems, defined by A. Bicadze in twodimensional case.